Current trends in radiation protection : on the occasion of the 11th International Congress of the International Radiation Protection Association, 23-28 May 2004, Madrid, Spain - Métivier, H., 1942- (EDP Sciences, 2004)
Organizers of the 11th IRPA International Congress have wished to take advantage of this occasion to launch a new series of books dedicated to review the current important problems of concern in radioprotection.